2022
DOI: 10.1111/2041-210x.13879
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the performance and efficiency of environmental DNA/RNA capture methodologies under controlled experimental conditions

Abstract: 1. Growing interest and affordability of environmental DNA and RNA (eDNA and eRNA) approaches for biodiversity assessments and monitoring of complex ecosystems have led to the emergence of manifold protocols for nucleic acids (NAs) isolation and processing. Although there is no consensus on a standard-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 89 publications
2
22
2
Order By: Relevance
“…In addition to non-specific amplification, extraction efficiency, reverse transcription efficiency of cDNA, and PCR bias should be validated to compare the copy numbers between DNA and RNA; however, avoiding these experimental biases is very difficult. Co-extraction, employed to minimize bias, is one of the best approaches to compare eDNA and eRNA and helps to reduce sampling bias. ,, Over the study period, fish DNA and RNA copy numbers in the influent and the effluent per sampling day were similar (Figure S2). The number of positive droplets in negative controls (negative filtration controls, netative co-extraction controls, and negative cDNA synthesis controls) was similar to that in negative controls (sterile distilled water).…”
Section: Resultsmentioning
confidence: 99%
“…In addition to non-specific amplification, extraction efficiency, reverse transcription efficiency of cDNA, and PCR bias should be validated to compare the copy numbers between DNA and RNA; however, avoiding these experimental biases is very difficult. Co-extraction, employed to minimize bias, is one of the best approaches to compare eDNA and eRNA and helps to reduce sampling bias. ,, Over the study period, fish DNA and RNA copy numbers in the influent and the effluent per sampling day were similar (Figure S2). The number of positive droplets in negative controls (negative filtration controls, netative co-extraction controls, and negative cDNA synthesis controls) was similar to that in negative controls (sterile distilled water).…”
Section: Resultsmentioning
confidence: 99%
“…Similar validation techniques can be used to develop eRNA metabarcoding as a quantitative or semi-quantitative method. There is growing interest in optimizing eRNA extraction protocols from different types of environmental media to standardize the use of eRNA in downstream molecular applications 55 . Thus, standardizing eRNA protocols will help with integration into environmental management toolkits for regulatory purposes.…”
Section: Discussionmentioning
confidence: 99%
“…Studies on human microbiome samples ( Gorzelak et al, 2015 ; Song et al, 2016 ) and eukaryotic eDNA ( Thomsen et al, 2012 ; Maruyama et al, 2014 ; Yamanaka et al, 2016 ) have shown changes in DNA yield and composition over relatively short time scales; however, other reports offer conflicting results on microbiome stability (e.g., Lauber et al, 2010 ). Environmental RNA is more prone to degradation than eDNA ( Marshall et al, 2021 ; Zaiko et al, 2022 ); thus, shorter filtration times are needed. If RNA is targeted for collection, limit filtration to 20 minutes to provide a practical timeframe to process multiple samples ( Zaiko et al, 2022 ) or 15 minutes to be in accordance with AtlantECO protocols ( Pesant et al, 2022 ).…”
Section: Logistic and Resource Considerationsmentioning
confidence: 99%
“…Environmental RNA is more prone to degradation than eDNA ( Marshall et al, 2021 ; Zaiko et al, 2022 ); thus, shorter filtration times are needed. If RNA is targeted for collection, limit filtration to 20 minutes to provide a practical timeframe to process multiple samples ( Zaiko et al, 2022 ) or 15 minutes to be in accordance with AtlantECO protocols ( Pesant et al, 2022 ).…”
Section: Logistic and Resource Considerationsmentioning
confidence: 99%
See 1 more Smart Citation